No Survival Benefit for Patients with Treatment in Certified Breast Centers—A Population‐based Evaluation of German Cancer Registry Data. Issue 5 (1st July 2015) - Schrodi, Simone; Tillack, Anett; Niedostatek, Antje; Werner, Carmen; Schubert‐Fritschle, Gabriele; Engel, Jutta
Abstract Much time and money has been spent on the establishment and preservation of certified breast centers (CBCs), but up to now there is almost no evidence for whether certification results in an improved outcome for breast cancer patients. The aim of this evaluation was to assess, whether the certification of specialized units had any influence on their patients' outcomes and if a survival difference between CBC patients and non‐CBC patients can be shown. This population‐based analysis included cancer registry data from 32, 789 operated breast cancer patients with no prior cancer diagnosis and with active follow‐up. They were diagnosed between 2004 and 2010 in four different regions in Germany. Survival was investigated using the Kaplan–Meier method and multivariate Cox regression analysis. A survival difference was found neither between patients with treatment before and after certification of specialized units nor between CBC patients and non‐CBC patients aged up to 75 years. Only for patients older than 75 years, an improved survival could be seen for CBC patients (adjusted hazard ratio 0.77; 95% confidence interval 0.68–0.87). The improved survival of elderly CBC patients is most likely caused by selection effects concerning health status differences and not by processes attributable to certification. Thus, this study found that as of yet, certification has not influenced survival of breast cancer patients.